Nano-carbon reinforced superfine cement-based blocking material as well as preparation method and application thereof

Through nanocarbon-enhanced ultrafine cement-based blocking materials, ultrafine grinding and airflow grading technology optimize particle distribution, the problem of difficulty in penetrating into micro cracks in the existing technology is solved, and efficient sealing and long-term stability are achieved. Improve the effect of groundwater pollution control in mining areas.

CN119409446AActive Publication Date: 2025-02-11SHANDONG UNIV

Patent Information

Application Number
CN202411512313.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-11
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively penetrate into the tiny cracks in the mining area, resulting in the unsatisfactory sealing effect after the sudden water rush accident in the mining area, and the inability to effectively control the groundwater flow channels and the diffusion of pollutants.

Method used

Using nanocarbon-enhanced ultrafine cement-based blocking material, this material optimizes particle distribution through ultrafine grinding technology and airflow grading technology, combining solid waste sintering active materials and multifunctional carbon quantum dot modified carbon nanotubes to improve the material permeability and early strength.

Benefits of technology

The material can effectively penetrate into tiny cracks and porous media, quickly seal the groundwater channel, prevent the spread of pollutants, and significantly improve the sealing effect and the durability and permeability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409446A_ABST
    Figure CN119409446A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of geotechnical engineering, and particularly relates to a nanocarbon reinforced superfine cement-based blocking material as well as a preparation method and application thereof. The superfine cement-based blocking material prepared by the invention is prepared by uniformly mixing 45-50 parts of cement, 0.5-2.5 parts of a solid waste sintered active material, 0-0.05 part of a water reducing agent, 0.015-0.1 part of carbon nanotubes, 0.5-2.5 parts of a 1% solution of carbon quantum dots and 45-50 parts of water. The material has relatively low porosity and is not dispersed; the high groutability is achieved, and the material can permeate into tiny holes; and it is guaranteed that the material has high strength, the crushed rock bonding and reinforcing strength is high, and the material has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of geotechnical engineering, and specifically relates to a nano-carbon reinforced ultrafine cement-based blocking material and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the deepening of mineral resource development, the issue of environmental protection in mining areas has become increasingly prominent. In particular, after a sudden water inrush accident in a mine, a large number of tiny cracks are often formed in the rock formation. These microcracks not only weaken the structural stability of the rock formation, but also provide convenient channels for groundwater infiltration, causing pollutants in the mining area to spread through these cracks, thereby polluting groundwater resources. This pollution not only threatens the ecological environment of the mining area, but also poses a potential threat to the safety of living water for surrounding residents.

[0004] At present, the commonly used grouting materials for plugging cracks after sudden water inrush accidents in mining areas are mostly based on traditional materials such as cement, chemical slurry or polymer. However, due to reasons such as large particles or poor fluidity, these materials are difficult to effectively penetrate into tiny cracks, resulting in unsatisfactory plugging effects. This limitation makes it impossible to effectively control the flow channels of groundwater, and pollutants can still continue to spread through unblocked cracks, thereby exacerbating environmental pollution problems.

[0005] To meet this challenge, technicians in this field urgently need to develop a new material that can penetrate into microcracks and effectively seal them. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a nano-carbon enhanced ultrafine cement-based blocking material and a preparation method and application thereof. The material prepared by the present invention has low porosity, is not dispersed, and has strong injectability, and can penetrate into tiny pores; and can ensure that the material has high strength, and has high bonding and reinforcement strength for crushed rock.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The first aspect of the present invention provides a nano-carbon enhanced ultrafine cement-based blocking material, which comprises, by weight, 45 to 50 parts of cement, 0.5 to 2.5 parts of solid waste sintering active materials, 0 to 0.05 parts of water reducer, 0.015 to 0.1 parts of carbon nanotubes, 0.5 to 2.5 parts of a 1% solution of carbon quantum dots, and 45 to 50 parts of water.

[0009] Preferably, the raw material composition of the ultrafine cement-based blocking material includes, by weight: 49 parts of cement, 1.0 parts of solid waste sintering active material, 0.05 parts of water reducer, 0.1 parts of carbon nanotubes, 0.5 parts of carbon quantum dot 1% solution, and 49.5 parts of water.

[0010] Preferably, the cement used is K700 (grade II) ultrafine cement with a fineness D90 of 18.3 μm.

[0011] Preferably, the solid waste sintering active material is selected from one or more of construction waste containing sulfoaluminate cement, coal gangue, fly ash and production by-products of sulfoaluminate cement; further preferably, the construction waste containing sulfoaluminate cement is calcined solid waste sulfoaluminate treated with ultrafine grinding technology and airflow classification technology.

[0012] Preferably, the carbon nanotubes are selected from one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, double-walled carbon nanotubes, open-ended carbon nanotubes and closed-ended carbon nanotubes.

[0013] Preferably, the 1% carbon quantum dot solution is prepared as follows: the weight ratio of solid carbon quantum dots (CQDs) to water is 1:100.

[0014] The second aspect of the present invention provides a method for preparing the above-mentioned nano-carbon enhanced ultrafine cement-based blocking material, comprising the following steps:

[0015] S1, mixing cement, solid waste sintering active materials and a water reducing agent to obtain a powder component;

[0016] S2, mixing carbon nanotubes, carbon quantum dots 1% solution and water to obtain a liquid component;

[0017] S3. Mix the powder component and the liquid component to obtain the ultrafine cement-based blocking material.

[0018] Preferably, in step S1, the weight ratio of the cement, the solid waste sintering active material and the water reducing agent is 45-50:0.5-2.5:0-0.05; and the water reducing agent is polycarboxylic acid high-efficiency water reducing agent powder.

[0019] Preferably, in step S2, the weight ratio of the carbon nanotubes and carbon quantum dots 1% solution to water is 0.015-0.1:0.5-2.5:45-50.

[0020] Preferably, in step S2, the powder components are mixed after the carbon nanotubes are fully dispersed in the mixed solution.

[0021] The third aspect of the present invention provides an application of the nano-carbon enhanced ultrafine cement-based blocking material described in the first aspect in the control and prevention of groundwater pollution in mining areas.

[0022] The beneficial effects achieved by one or more technical solutions of the present invention are as follows:

[0023] (1) The ultrafine high-efficiency cement-based blocking material prepared by the present invention is graded and optimized by ultrafine grinding technology, which significantly improves the permeability of the material and can effectively penetrate into the micro-cracks and porous media in the mining area. The material can quickly block tiny underground water channels and prevent pollutants from spreading with the water flow, and is particularly suitable for emergency treatment after sudden water inrush accidents in mining areas.

[0024] Among them, ultrafine grinding and airflow classification treatment optimize the uniformity and distribution of particles, making the particle size more concentrated, so that it can penetrate into smaller pores and cracks, and improve the injectability of grouting materials. Smaller particle sizes are easier to fill micropores in the material, reduce the overall porosity, and enhance the density of the material. Airflow classification removes larger particles, reduces friction and obstruction between particles, reduces the viscosity of the slurry, and improves the fluidity of the slurry.

[0025] (2) The present invention uses highly efficient solid waste sintered active materials, which enable the materials to quickly solidify and obtain high early strength after grouting, effectively forming a stable blocking barrier to prevent groundwater leakage. The high early strength performance of the material ensures that the blocking operation can be completed in a short time, preventing the spread of groundwater pollution to the greatest extent.

[0026] (3) The present invention utilizes the volcanic ash effect and microscopic gelation hydration mechanism to greatly improve the durability and impermeability of the material after solidification. Through the active reaction of the volcanic ash material, the internal structure of the material is more compact, which enhances its crack resistance and water erosion resistance, and ensures the long-term stability of the material in complex underground environments.

[0027] (4) The present invention uses ultrafine solid waste sintered active materials as reinforcing components, which not only effectively improves the physical and mechanical properties of the material, but also realizes the resource utilization of solid waste, reduces material costs, and meets the requirements of sustainable development.

[0028] (5) The present invention introduces self-developed multifunctional carbon quantum dots to modify carbon nanotubes as surface enhancers. In unmodified CNTs, strong van der Waals forces cause carbon nanotubes to aggregate into bundles, making them difficult to disperse in liquid media or matrices. CQDs physically adsorb by stacking with the π-π bonds on the surface of CNTs, shielding the van der Waals forces between the tubes and preventing them from entangled or agglomerating with each other. These multifunctional enhancers not only improve the dispersibility of the material, but also enhance the early strength and bonding properties of the material through synergistic effects with the matrix, while further enhancing the material's anti-penetration properties and overall durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0030] Figure 1 This is a physical picture of the grouting material stone body prepared in Example 1 of the present invention;

[0031] Figure 2 This is a comparison diagram of particle size distribution of ultrafine cement and solid waste sintered active materials used in the embodiment of the present invention before and after ultrafine grinding and airflow classification technology treatment;

[0032] Figure 3 A comparison chart of the compressive strength test of the ultrafine cement-based blocking material prepared in the embodiment of the present invention and the comparative example;

[0033] Figure 4 The figure is a comparison chart of rheological properties test of ultrafine cement-based blocking materials prepared in the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION

[0034] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0035] In view of the increasingly serious problem of groundwater pollution caused by micro-crack seepage in mining areas, the micro-cracks and pore structures of the rock formations in mining areas are complex, water flow is difficult to effectively block, and conventional materials are difficult to meet the requirements of long-term water blocking and blocking effects. Therefore, the present invention proposes an ultra-fine cement-based blocking material and a preparation method and application. The material prepared by the present invention can effectively fill micro-cracks through the penetration ability and high early strength characteristics of ultra-fine particles, forming a continuous and dense water-blocking barrier, preventing the further spread of polluted water, and ensuring the safety and stability of the groundwater system.

[0036] The first typical embodiment of the present invention provides a nanocarbon-enhanced ultrafine cement-based blocking material, whose raw material composition includes, by weight: 45 to 50 parts of cement, 0.5 to 2.5 parts of solid waste sintering active materials, 0 to 0.05 parts of water reducer, 0.015 to 0.1 parts of carbon nanotubes, 0.5 to 2.5 parts of 1% carbon quantum dot solution, and 45 to 50 parts of water.

[0037] In one or more examples of this implementation, the raw material composition of the ultrafine cement-based blocking material includes: 1.0 parts of solid waste sintering active material, 0.05 parts of water reducer, 0.1 parts of carbon nanotubes, 0.5 parts of carbon quantum dot 1% solution, and 49.5 parts of water.

[0038] In one or more examples of this implementation mode, the cement used is K700 (grade II) ultrafine cement with a fineness D90 of 18.3 μm and implemented in accordance with standards Q / K0001-2015 and GB / T35161-2017.

[0039] In one or more examples of this embodiment, the solid waste sintering active material is selected from one or more of construction waste containing sulfoaluminate cement, coal gangue, fly ash and production by-products of sulfoaluminate cement; further preferably, the construction waste containing sulfoaluminate cement is calcined solid waste sulfoaluminate treated with ultrafine grinding technology and airflow classification technology.

[0040] In one or more examples of this implementation, the carbon nanotubes are selected from one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, double-walled carbon nanotubes, open-ended carbon nanotubes and closed-ended carbon nanotubes.

[0041] In one or more examples of this embodiment, the 1% carbon quantum dot solution is prepared as follows: the volume ratio of solid carbon quantum dots (CQDs) to water is 1:100.

[0042] A second typical embodiment of the present invention provides a method for preparing the above-mentioned nano-carbon enhanced ultrafine cement-based blocking material, comprising the following steps:

[0043] S1, mixing cement, solid waste sintering active materials and a water reducing agent to obtain a powder component;

[0044] S2, mixing carbon nanotubes, carbon quantum dots 1% solution and water to obtain a liquid component;

[0045] S3. Mix the powder component and the liquid component to obtain the ultrafine cement-based blocking material.

[0046] In one or more examples of this implementation mode, in step S1, the weight ratio of the cement, the solid waste sintering active material and the water reducer is 45-50:0.5-2.5:0-0.05; and the water reducer is polycarboxylic acid high-efficiency water reducer powder.

[0047] In one or more examples of this implementation mode, in step S2, the weight ratio of the carbon nanotubes and carbon quantum dots 1% solution to water is 0.015-0.1:0.5-2.5:45-50.

[0048] In one or more examples of this implementation mode, in step S2, the powder components are mixed after the carbon nanotubes are fully dispersed in the mixed solution.

[0049] A third typical embodiment of the present invention provides an application of the above-mentioned nano-carbon enhanced ultrafine cement-based blocking material in the control and prevention of groundwater pollution in mining areas.

[0050] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0051] Embodiment 1: This embodiment provides a nano-carbon enhanced ultrafine cement-based blocking material and a preparation method thereof, comprising the following steps:

[0052] Step 1: Weigh the powder components by mass, including the following components: 49 parts of ground ultrafine cement, 1 part of solid waste sintering active material, and 0.05 parts of water reducing agent;

[0053] Step 2: Prepare liquid components by mass, including 0.5 parts of 1% carbon quantum dot solution, 0.1 parts of carbon nanotubes, and 49.5 parts of water;

[0054] Step 3: fully stir the weighed raw materials according to the preparation method of the composite material;

[0055] Step 4: Remove part of the material after stirring for fluidity test and rheological property test, pour the remaining material into the mold and place it in a 20°C environment for curing for up to 28 days.

[0056] Step 5: Test the compressive strength and porosity of the cured test blocks.

[0057] Embodiment 2: This embodiment provides a nano-carbon enhanced ultrafine cement-based blocking material and a preparation method thereof, comprising the following steps:

[0058] Step 1: Weigh the powder components by mass, including the following components: 50 parts of ground ultrafine cement, 0.5 parts of solid waste sintering active materials, and 0.05 parts of water reducing agent.

[0059] Step 2: Prepare liquid components by mass, including 1.5 parts of 1% carbon quantum dot solution, 0.015 parts of carbon nanotubes, and 48.5 parts of water.

[0060] Step 3: Fully stir the raw materials weighed above according to the preparation method of the composite material.

[0061] Step 4: Remove part of the material after stirring for fluidity test and rheological property test, pour the remaining material into the mold and place it in a 20°C environment for curing for up to 28 days.

[0062] Step 5: Test the compressive strength and porosity of the cured test blocks.

[0063] Embodiment 3: This embodiment provides a nano-carbon enhanced ultrafine cement-based blocking material and a preparation method thereof, comprising the following steps:

[0064] Step 1: Weigh the powder components by mass, including the following components: 48 parts of ground ultrafine cement, 1.5 parts of solid waste sintering active materials, and 0.05 parts of water reducing agent.

[0065] Step 2: Prepare liquid components by mass, including 1.5 parts of 1% carbon quantum dot solution, 0.015 parts of carbon nanotubes, and 48.5 parts of water.

[0066] Step 3: Fully stir the raw materials weighed above according to the preparation method of the composite material.

[0067] Step 4: Remove part of the material after stirring for fluidity test and rheological property test, pour the remaining material into the mold and place it in a 20°C environment for curing for up to 28 days.

[0068] Step 5: Test the compressive strength and porosity of the cured test blocks.

[0069] Embodiment 4: This embodiment provides a nano-carbon enhanced ultrafine cement-based blocking material and a preparation method thereof, comprising the following steps:

[0070] Step 1: Weigh the powder components by mass, including the following components: 46 parts of ground ultrafine cement, 2 parts of solid waste sintering active materials, and 0.05 parts of water reducing agent.

[0071] Step 2: Prepare liquid components by mass, including 2.5 parts of 1% carbon quantum dot solution, 0.015 parts of carbon nanotubes, and 45.5 parts of water.

[0072] Step 3: Fully stir the raw materials weighed above according to the preparation method of the composite material.

[0073] Step 4: Remove part of the material after stirring for fluidity test and rheological property test, pour the remaining material into the mold and place it in a 20°C environment for curing for up to 28 days.

[0074] Step 5: Test the compressive strength and porosity of the cured test blocks.

[0075] Embodiment 5: This embodiment provides a nano-carbon enhanced ultrafine cement-based blocking material and a preparation method thereof, comprising the following steps:

[0076] Step 1: Weigh the powder components by mass, including the following components: 47 parts of ground ultrafine cement, 2.5 parts of solid waste sintering active materials, and 0.05 parts of water reducing agent.

[0077] Step 2: Prepare liquid components by mass, including 2.5 parts of 1% carbon quantum dot solution, 0.035 parts of carbon nanotubes, and 47 parts of water.

[0078] Step 3: Fully stir the raw materials weighed above according to the preparation method of the composite material.

[0079] Step 4: Remove part of the material after stirring for fluidity test and rheological property test, pour the remaining material into the mold and place it in a 20°C environment for curing for up to 28 days.

[0080] Step 5: Test the compressive strength and porosity of the cured test blocks.

[0081] Comparative Example 1: The components are different from those in Example 1 in that the cement type in step 1 is Conch brand 425 ordinary Portland cement (ordinary cement) with a fineness D90 of 75.6 μm, and the other components are the same as those in Example 1; the preparation steps are consistent with those in Example 1.

[0082] Comparative Example 2: The components are different from those of Example 1 in that no solid waste sintering active material is added in step 1, and the other components are the same as those of Example 1; the preparation steps are consistent with those of Example 1.

[0083] Comparative Example 3: The difference between the components of Example 1 and those of Example 1 is that the solid waste sintering active material in step 1 has not been treated with ultrafine grinding technology and airflow classification technology (ordinary inorganic early strength agent), and the other components are the same as those of Example 1; the preparation steps are consistent with those of Example 1.

[0084] Comparative Example 4: The difference from Example 1 is that the dispersant type in step 2 is carbon nanotube PMA dispersion, and the other components are the same as those in Example 1; the preparation steps are consistent with those in Example 1.

[0085] Comparative Example 5: The components are different from those in Example 1 in that the amounts of carbon quantum dots and carbon nanotubes added in step 2 are 2.5 parts and 0.2 parts respectively, and the other components are the same as those in Example 1; the preparation steps are consistent with those in Example 1.

[0086] Comparative Example 6: The difference between the components of Example 1 is that no carbon quantum dot dispersant is added in step 2, and the other components are the same as those of Example 1; the preparation steps are consistent with those of Example 1.

[0087] Test Example 1: This test example is to test the fluidity, porosity, compressive strength and cost of the ultrafine cement-based blocking materials prepared in the examples and comparative examples, as shown in Table 1 and Figure 3 As shown:

[0088] Table 1

[0089]

[0090] From the data in Table 1, we can see that:

[0091] Compared with Comparative Example 1, it can be seen that the fineness of ordinary cement is too high (such as Figure 2As shown in the figure, the grouting material cannot penetrate into the tiny cracks, and it is easy to form large particles in the slurry, which increases the shear resistance and leads to increased viscosity, making it difficult to meet the performance requirements;

[0092] Compared with Comparative Example 2, it can be seen that not adding solid waste sintering active materials or adding low amounts will lead to reduced anti-seepage performance of the blocking material, making it difficult to meet performance requirements; and without adding inorganic early strength agent (solid waste sintering active materials), the synergistic mechanism with the organic early strength agent (carbon nanotubes) cannot be exerted, resulting in a continuous increase in material viscosity;

[0093] Compared with Comparative Examples 1 and 3, it can be seen that the treatment effect of ultrafine grinding and airflow classification on cement and early strength agent can greatly optimize the particle size distribution, reduce the overall particle size, and thus improve the fluidity of the slurry and reduce the overall porosity (such as Figure 2 Based on this, the present invention adds an early strength agent to improve the overall performance of the material;

[0094] Compared with Comparative Examples 4 to 5, it can be seen that, on the basis of meeting the basic performance, excessive addition of carbon nanotubes and carbon quantum dots leads to increased costs and easy agglomeration, which affects the overall performance;

[0095] Compared with Comparative Example 6, it can be seen that when no carbon quantum dot dispersant is added, in the unmodified CNTs, due to the large specific surface area and strong van der Waals force of carbon nanotubes, it is easy for the particles to attract each other and agglomerate to form larger agglomerates. These agglomerates will increase the shear resistance in the slurry, increase the viscosity of the slurry, and significantly reduce the fluidity of the material.

[0096] Therefore, it is necessary to control the weight proportions of cement and early strength agent (solid waste sintering active material, carbon nanotubes) within this range, which can ensure that the grouting material has higher strength and higher injectability without increasing costs.

[0097] like Figure 4 As shown, the viscosity time-varying curve is a curve that reflects the law of material viscosity variation over time, and is used to analyze the evolution of the viscosity of the material over time under static or shear stress. Normally, the addition of an early strength agent will accelerate the hydration reaction. During this process, the internal structure of the material changes rapidly, resulting in a rapid increase in viscosity, a decrease in fluidity, and a faster formation of a solidified structure. In Examples 1 to 5, when appropriate weight portions of inorganic early strength agents and organic early strength agents are added, the viscosity of the material only shows a small increase in the initial stage of the reaction, and then the viscosity of the material remains stable over time, indicating that the fluidity of the material under stress conditions is relatively constant and the injectability is good.

[0098] Application Example 1:

[0099] The grouting reinforcement test simulates the actual reinforcement process in a laboratory environment and is used to study and verify the performance of grouting materials, reinforcement effects and technical parameters. This process can help optimize the actual construction plan and ensure the success of the reinforcement work.

[0100] After adding coarse / fine aggregates into the cylindrical acrylic tube, use permeable stone to seal the two ends of the tube and put it into the grouting fixture. Disperse CNTs in the CQDs solution in a plastic beaker, add it to the stirring pot after ultrasonic treatment for 5 minutes, add ultrafine cement, solid waste early strength agent and water reducer in turn, stir thoroughly for 2 minutes according to the stirring procedure, and then use a manual pressure pump to inject into the acrylic tube at a pressure of 1.5MPa.

[0101] According to the test report, the 28d compressive strength of the grouting reinforcement body can reach 15.6MPa, and the 28d flexural strength can reach 2.3MPa, showing good bonding and reinforcement ability for crushed rock (model such as Figure 1 shown).

[0102] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A nano-carbon enhanced ultrafine cement-based blocking material, characterized in that: The raw material composition includes, by weight: 45-50 parts of cement, 0.5-2.5 parts of solid waste sintering active materials, 0-0.05 parts of water reducer, 0.015-0.1 parts of carbon nanotubes, 0.5-2.5 parts of 1% carbon quantum dot solution, and 45-50 parts of water.

2. The nanocarbon-enhanced ultrafine cement-based blocking material according to claim 1, characterized in that: The raw material composition of the ultrafine cement-based blocking material includes, by weight: 49 parts of cement, 1.0 parts of solid waste sintering active material, 0.05 parts of water reducer, 0.1 parts of carbon nanotubes, 0.5 parts of carbon quantum dot 1% solution, and 49.5 parts of water.

3. The nanocarbon-enhanced ultrafine cement-based blocking material according to any one of claims 1 to 2, characterized in that: The cement used is K700 ultrafine cement with a fineness D90 of 18.3 μm; the solid waste sintering active material is selected from one or more of construction waste containing sulphoaluminate cement, coal gangue, fly ash and production byproducts of sulphoaluminate cement.

4. The nanocarbon-enhanced ultrafine cement-based blocking material according to claim 3, characterized in that: The construction waste containing sulphoaluminate cement is calcined solid waste sulphoaluminate that has been processed by ultrafine grinding technology and airflow classification technology.

5. The nanocarbon-enhanced ultrafine cement-based blocking material according to any one of claims 1 to 2, characterized in that: The carbon nanotubes are selected from one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, double-walled carbon nanotubes, open-ended carbon nanotubes and closed-ended carbon nanotubes.

6. The nanocarbon-enhanced ultrafine cement-based blocking material according to any one of claims 1 to 2, characterized in that: The 1% carbon quantum dot solution is prepared as follows: the volume ratio of solid carbon quantum dots to water is 1:

100.

7. A method for preparing the nanocarbon-enhanced ultrafine cement-based blocking material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, mixing cement, solid waste sintering active materials and a water reducing agent to obtain a powder component; S2, mixing carbon nanotubes, carbon quantum dots 1% solution and water to obtain a liquid component; S3. Mix the powder component and the liquid component to obtain the ultrafine cement-based blocking material.

8. The preparation method according to claim 7, characterized in that: In step S1, the weight ratio of the cement, the solid waste sintering active material and the water reducing agent is 45-50:0.5-2.5:0-0.05; the water reducing agent is polycarboxylic acid high-efficiency water reducing agent powder; Preferably, in step S2, the weight ratio of the carbon nanotubes and carbon quantum dots 1% solution to water is 0.015-0.1:0.5-2.5:45-50.

9. The preparation method according to claim 7, characterized in that: In step S2, after the carbon nanotubes are fully dispersed in the mixed solution, the powder components are mixed.

10. Use of the nanocarbon-enhanced ultrafine cement-based blocking material according to any one of claims 1 to 6 in the control and prevention of groundwater pollution in mining areas.

Citation Information

Patent Citations

  • Carbon nano-tube cement-based waterproof material and preparation method thereof

    CN102603235A

  • Mine fracture grouting material and usage method thereof

    CN102757206A

  • Graphene quantum dot / carbon nanotube / PEDOT:PSS composite film and preparation method thereof

    CN106810823A

  • Method for dispersion of multi-walled carbon nanotubes

    CN110629242A

  • Grouting material based on industrial-grade graphene oxide and preparation method thereof

    CN113149540A

Cited By

  • Cement raw material mineralizer with photocatalytic excitation mineralization effect and preparation method and application thereof

    CN119977370A

  • A mineralizer for raw cement meal with photocatalytic excitation mineralization effect, its preparation method and application

    CN119977370B